Proceedings of INFOCOM '97
DOI: 10.1109/infcom.1997.631137
|View full text |Cite
|
Sign up to set email alerts
|

Proactive network fault detection

Abstract: The increasing role of communication networks in today's society results in a demand for higher levels of network availability and reliability. At the same time, fault management is becoming more dificult due to the dynamic nature and heterogeneity of networks. We propose an intelligent monitoring system using adaptive statistical techniques. The system continually learns the normal behavior of the network and detects deviations from the norm. Within the monitoring system, the measurements are segmented, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
1

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 16 publications
(5 reference statements)
0
79
1
Order By: Relevance
“…Managing complex hardware and software systems has always been a difficult task. The Internet and the proliferation of web-based services have increased the importance of this task, while aggravating the problem (faults) in at least four ways (Meira, 1997;Thottan & Ji, 1998;Hood & Ji, 1997a;Lazar et al, 1992):…”
Section: Causes Of Cellular Network Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing complex hardware and software systems has always been a difficult task. The Internet and the proliferation of web-based services have increased the importance of this task, while aggravating the problem (faults) in at least four ways (Meira, 1997;Thottan & Ji, 1998;Hood & Ji, 1997a;Lazar et al, 1992):…”
Section: Causes Of Cellular Network Faultsmentioning
confidence: 99%
“…The main reasons why Bayesian networks was chosen for cellular network faults prediction include (Hood et al, 1997a), (Hood et al, 1997b), (Hood et al, 1998):…”
Section: Bayesian Networkmentioning
confidence: 99%
“…In the figure, at the point marked by the red circle, p = 7 indicates that there are 7 links experiencing anomalies at that point. Furthermore, q = (2545) 10 = (100111110001) 2 at that point indicates that #links 1,5,6,7,8,9, and 12 are experiencing anomalies. We mark these detected links with red lines on the shortest route tree, and get the anomaly propagation path shown in Fig.…”
Section: Validation Of Tracingmentioning
confidence: 99%
“…Early efforts were focused on the practical problem of network fault detection [7], [8], and in using time series methods to detect traffic anomalies [9], [4]. Several studies have shown that entropy-based methods can be effective for anomaly detection [10], [11] including Xu et al who use entropy to classify traffic in packet traces taken from an ISP backbone [12].…”
Section: Related Workmentioning
confidence: 99%